Tinjauan Yuridis Perlindungan Hukum Bagi Petani Kelapa Dalam Transaksi Jual Beli Kelapa (Studi di Gudang Kelapa Do’a Ibu Kecamatan Tembilahan) - Raudah; Wandi; Fitri Wahyuni (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2025)
Coconuts are a strategic commodity in Indragiri Hilir, but farmers often find themselves in a weak bargaining position in the value chain. Key problems include price non-transparency, detrimental quality variations, unreasonable weight discounts, and limited access to dispute resolution. These conditions indicate that legal protection for farmers at the Do’a Ibu Coconut Warehouse in Tembilahan District is suboptimal. This study formulates two main questions: (1) What is the legal review of the legal protection for coconut farmers in coconut buying and selling transactions? (2) What are the obstacles to legal protection for coconut farmers at the Do’a Ibu Coconut Warehouse? The method used is a normative-juridical approach with an empirical dimension, with the research location being Gudang Kelapa Do’a Ibu, Tembilahan. Primary data was obtained through interviews and observations using purposive sampling, while secondary data came from laws and regulations and related documents. All data were analyzed qualitatively. The results indicate that despite preventive and repressive protection measures being in place, transparency and final price guarantees have not been optimally met, leaving farmers as powerless price takers. Massive consumer rights awareness-raising, systematic implementation of price transparency by business actors, and technical regulatory reform are needed to close the gap in post-transaction accountability.